Empowerment of Digital Marketing -Based MSMEs through Creative Content Training for Youth Youth Organization - Apriyanto, Apriyanto; Lee, Ava; Farah, Rina (Journal Ligundi of Community Service, 2025)
Background. Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting local economies, particularly in rural and suburban areas. However, many MSMEs still face challenges in utilizing digital marketing effectively due to limited digital literacy and lack of creative content. Purpose. This study aims to empower MSMEs by providing training in creative content development to members of the youth organization (Karang Taruna) in a target village. The training is designed to equip youth with digital marketing skills, enabling them to assist local MSMEs in promoting their products through social media platforms such as Instagram, TikTok, and Facebook. Method. This community engagement project utilized the Participatory Action Research (PAR) method, involving planning, implementation, observation, and reflection phases. Data collection was conducted through pre- and post-training questionnaires, observation, and focus group discussions. A total of 25 youth members participated in the training sessions over a four-week period. Results. The findings show a significant improvement in participants’ ability to create engaging digital content, including product photography, video editing, and storytelling techniques. Furthermore, three local MSMEs reported increased visibility and engagement on their social media accounts after receiving content support from trained youth. Conclusion. In conclusion, creative content training has proven effective in empowering youth to become agents of digital transformation for MSMEs. This model may serve as a replicable strategy to enhance the digital economy at the grassroots level.